Changes in airway function and bronchial responsiveness after acute occupational exposure to chlorine leading to treatment in a first aid unit. Issue 5 (May 1998) - Leroyer, C; Malo, J L; Infante-Rivard, C; Dufour, J G; Gautrin, D
Abstract : OBJECTIVES: To describe the baseline characteristics and the time course of changes in lung function in workers accidentally inhaling high concentrations of chlorine in a prospective study. METHODS: Baseline spirometry and methacholine challenge test were performed in a cohort of 278 workers at risk of accidental inhalation of chlorine. Workers in whom accidental inhalation led to intervention in a first aid unit were reassessed five to 25 days after the accident and serially thereafter when there where notable changes. RESULTS: During a four year follow up period, 13 workers were seen at the first aid unit after a symptomatic accidental inhalation. Three of them experienced notable functional changes: one worker experienced a 10% fall in forced expiratory volume in one second (FEV1), and the other two had a notable fall in the concentration of methacholine that caused a 20% fall in FEV1 (PC20). Two workers were smokers and one had a personal history of atopy. Baseline assessment was within the normal range in these three workers. Recovery was complete three months after the accidental inhalation. CONCLUSION: Transient but notable decreases in airway function or increases in bronchial responsiveness can occur after an accidental inhalation of high concentrations of chlorine in workers at risk.